PENGARUH JOB INSECURITY, BUDAYA ORGANISASI, DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASIONAL - Gunawan, I Ketut Agus Pande; Ardana, I Komang (E-Jurnal Manajemen; Vol 9 No 5 (2020), 2020)
Organizational commitment is an attitude that reflects employee loyalty to the organization, and an ongoing process in which employees express their concern for the organization, success, and prosperity. The purpose of this study is to explain the effect of job insecurity, organizational culture, and work environment on organizational commitment. This research was conducted at Artha Agung Resort and Restaurant, Jl. Raya Besakih, Menanga, Karangasem with a quantitative approach in the form of associative. The sample technique used is the saturated sample technique and the data collection method using a survey approach with a questionnaire method that is measured using a Likert scale. A sample of 31 employees. Multiple linear regression analysis technique. Based on the results of this study indicate that job insecurity has a significant negative effect on organizational commitment, and organizational culture, and the work environment has a significant positive effect on organizational commitment. Keywords : Work Insecurity, Organizational Culture, Work Environment, Organizational Commitment